Analysis of the mechanical properties and micro-reinforcement mechanisms of loose accumulated sandy soil improved with polyvinyl alcohol and sisal fiber - Sang, Ding; Wang, Peiqing; Chen, Liang; Zhang, Wengang; Liu, Zhen; Wang, Qi (Frontiers in Physics, 2024)
As one of the world’s most fragile and sensitive ecological regions, Xizang risks significant environmental damage from using traditional materials, including cement and lime, to improve and reinforce loose accumulated sandy soil slopes. To address this issue, this study utilized a low-concentration biodegradable polyvinyl alcohol (PVA) solution combined with sisal fibers (SFs) to stabilize loose accumulated sand in southeastern Xizang. A series of physical, mechanical, and microscopic analyses was conducted to evaluate the properties of the treated sand. The results indicated the following. 1) The stress-strain curves of the improved samples exhibited an elastic-plastic relationship. Failure was observed in two stages. At a strain of 3% or less, the samples demonstrated elastic deformation with a linear increase in stress, whereas the deviator stress increased rapidly and linearly with an increase in axial strain. Once the strain exceeded 3%, the deformation became plastic with a nonlinear increase in the stress-strain relationship, and the growth rate of the deviator stress gradually decreased and leveled off. 2) Under varying confining pressure conditions, the relationship curve between the maximum (σ1-σ3)max∼σ3 for both untreated loose accumulated sandy soil and soil improved with the PVA solution, and the sisal fiber was approximately linear. 3) The SFs created a skeletal-like network that encased the soil particles, and the hydroxyl functional groups in the PVA molecules bonded with both the soil particles and the fiber surface, thereby enhancing the interfacial properties. This interaction resulted in a tighter connection between the soil particles and SFs, which improved the stability of the structure. 4) The incorporation of a PVA solution and SFs significantly enhanced the mechanical strength and deformation resistance of the loose accumulated sandy soil. The optimal ratio for the improved soil was SP = 3% and SL = 15 mm, which increased the cohesion from 24.54 kPa in untreated loose accumulated sandy soil to 196.03 kPa. These findings could be applied in engineering practices to improve and reinforce loose accumulated sandy soil slopes in southeastern Xizang and provide a theoretical basis for such applications.